(untitled) (Ágora Journal, 2026)
This article discusses the issues surrounding the constitution of the Argentine national state in the late nineteenth century, considering the political and intellectual activity of the men who led this process. It analyzes the trajectory of the generations of 1837 and 1880, their convergences and divergences regarding the nation-building project, marked by scientistic thought, the promotion of European immigration, and the encouragement of public education. It also examines the configuration of reading fields and the development of the press in Argentina, with emphasis on the creation of historical and intellectual journals, especially the Revista de Derecho, Historia y Letras, founded by Estanislao Severo Zeballos, as an instrument of intervention in the political and cultural debate of the period.